What is polynomial ax^3+bx^2+cx+d if divided by (x-1),(x+1),(x+2), the reminder is always 3?
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
The polynomial ax^3 + bx^2 + cx + d is the product of the terms (x-1), (x+1) and (x+2) to which the remainder 3 is added.
(x - 1)(x...
(The entire section contains 76 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- What is the reminder when f(x)=x^5+x^4+1 is divided by g(x)=(x-1)^3 ?
- 1 Educator Answer
- Solve for x and y x^3-y^3=7 x^2+xy+y^2=7
- 2 Educator Answers
- (x-9)^1/4-(x+2)^1/3=-1 Find x !
- 1 Educator Answer
- Determine the quadratic ax^2+bx+c, if a,b,c are terms of arithmetic sequence. a=2t-3,b=5t+1,c=4t-7
- 1 Educator Answer
- Determine the expression of the equation 2x^3-x^2+ax+b=0 if a solution is 1+i .
- 1 Educator Answer
We'll note the polynomial P(X) = aX^3+bX^2+cX+d.
We'll write the reminder theorem, when P(x) is divided by (X-1):
P(1)=3
We'll write the reminder theorem, when P(x) is divided by (X+1):
P(-1)=3
We'll write the reminder theorem, when P(x) is divided by (X+2):
P(-2)=3
From these facts, we notice that the reminder of the division of P(x) to the product of polynomials (X-1)(X+1)(X+2) is also 3.
We'll write the reminder theorem:
aX^3+bX^2+cX+d=(X-1)(X+1)(X+2) + 3
We'll remove the brackets:
aX^3+bX^2+cX+d=(X^2-1)(X+2) +3
aX^3+bX^2+cX+d = X^3 + 2X^2-X -2 + 3
We'll combine like terms and we'll get:
aX^3 + bX^2 + cX + d = X^3 + 2X^2 - X + 1
P(X) = X^3 + 2X^2 - X + 1
Student Answers